Gamma irradiation preserves nutritional and chemical composition of Agaricus bisporus Portobello - Cardoso, Rossana V.C. (2019)
Mushrooms are being increasingly produced and consumed, but their high perishability still represents a major drawback for commercial purposes. Besides the main effect of increasing the product shelf-life, the conservation technologies should be the most innocuous possible for the consumers. Among the current approaches, irradiation technologies seem to represent interesting alternatives [1, 2]. The present work reports the effects of gamma radiation (1, 2 and 5 kGy) and storage time (0, 4 and 8 days at 5 °C) on the nutritional (moisture, fat, proteins, ash, carbohydrates and energy) and chemical composition (free sugars, ergosterol, tocopherols, organic acids and fatty acids) of Agaricus bisporus Portobello fresh samples, andthe results were compared with control samples (0 kGy, non-irradiated). The irradiation was performed in a Co-60 experimental four sources chamber. The proximate composition was evaluated by AOAC official procedures. Free sugars, ergosterol and tocopherols were determined using high performance liquid chromatography coupled to a refraction index, UV and fluorescence detector, respectively; organic acids were determined using ultrafast liquid chromatography coupled to a diode array detector, while fatty acids were determined using a gas chromatography coupled to a flame ionization detector [3]. Irradiation dose did not exert any remarkably negative effect over the nutritional parameters of stored (up to 8 days) Portobello samples, specifically the irradiated samples at 5 kGy indicated a preserved nutritional profile with the highest levels of protein. It was possible to observe the maintenance of fructose, mannitol and trehalose contents in the irradiated samples, along storage time. All the applied doses also preserved the total organic acids (oxalic, quinic and malic acids) in relation to the control sample. A higher ergosterol level was found in samples irradiated at 2 kGy, while the highest percentages of C16:0 (8.6%) were found in samples treated with 5 kGy. Gamma irradiation was effective in maintaining nutritional and chemical profiles throughout the assayed time intervals. Accordingly, this technology might represent an effective preservation approach for Portobello mushrooms.